2021
DOI: 10.1109/tcsvt.2020.3042882
|View full text |Cite
|
Sign up to set email alerts
|

Camcording-Resistant Forensic Watermarking Fallback System Using Secondary Watermark Signal

Abstract: Forensic watermarking is used to track down digital pirates after they illegally redistribute video content. Although existing algorithms often resist common signal processing attacks, they are not always robust against camcording attacks. As a solution in the state of the art, registration methods are used to align the attacked video to the original one. However, watermark detection still fails when the quality is sufficiently decreased or when exposed to targeted attacks. Therefore, this paper proposes a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…The core idea of the proposed method is to perform fallback watermark detection using perceptual hashes of secondary watermarks. This is much faster in comparison with using the uncompressed secondary watermark signals, which is done in our previous work [4]. Additionally, perceptual hashes require much less storage.…”
Section: Methodsmentioning
confidence: 93%
See 4 more Smart Citations
“…The core idea of the proposed method is to perform fallback watermark detection using perceptual hashes of secondary watermarks. This is much faster in comparison with using the uncompressed secondary watermark signals, which is done in our previous work [4]. Additionally, perceptual hashes require much less storage.…”
Section: Methodsmentioning
confidence: 93%
“…To improve the robustness of existing uncompressed-domain watermarking methods, our previous work proposed a fallback detection method that aims to detect the watermark when the traditional watermarking method cannot [4]. First, it was demonstrated that a secondary watermark signal is automatically and indirectly created during compression of a video with a primary watermark that was embedded by an existing method.…”
Section: Fallback Detection Using Secondary Watermarkmentioning
confidence: 99%
See 3 more Smart Citations